Relationship between stress hyperglycemia ratio and progression of non target coronary lesions: a retrospective cohort study - Shiqi Liu; Ziyang Wu; Gaoliang Yan; Yong Qiao; Yuhan Qin; Dong Wang; Chengchun Tang (Diabetology & Metabolic Syndrome)
Abstract Background Stress hyperglycemia ratio is a novel indicator of acute coronary synthesis (ACS), which is closely related to the severity and complications of ACS and other cardiovascular diseases. However, its relationship with the progression of non target coronary lesions remains unclear. The purpose of this paper is to explore the relationship between stress hyperglycemia ratio and the progression of non target coronary lesions. Methods This study retrospectively enrolled patients diagnosed with acute coronary syndrome who underwent stent implantation and follow-up evaluations by coronary angiography at Zhongda Hospital between January 2019 and January 2024. Patients were classified into progression and non progression groups based on follow-up angiography findings. Logistic regression models, restricted cubic spline analysis, and machine learning algorithms (LightGBM, decision tree, and XGBoost) were utilized to analyse the relationship of stress hyperglycemia ratio and non target lesion progression. Results A total of 1,234 ACS patients were included; 29.1% experienced non target lesions progression. Logistic regression analysis showed that stress hyperglycemia ratio (SHR) was a risk factor for non target disease progression (P < 0.001), and after adjusting for other variables, SHR was still independently associated with non target disease progression (OR = 2.12, 95% CI: 1.30–3.44, p = 0.003). RCS analysis revealed a near-linear relationship between SHR and nontarget lesions progression (P = 0.14). With the increase of SHR, the risk of non target lesions progression continued to increase, and the risk was significant when the SHR was greater than 0.96, but tended to be stable when the SHR was greater than 1.36 (p = 0.0047). A hybrid model combining logistic regression and XGBoost yielded the best predictive performance, with an AUC of 0.78 (95% CI: 0.72–0.85), incorporating SHR, number and stenosis severity of non target lesions (NTLs), hypertension and high-density lipoprotein cholesterol (HDL-c). Subgroup analysis showed that elevated SHR was a stronger predictor of NTL progression in non-diabetic patients (OR = 3.76, p = 0.007) compared with diabetic patients (OR = 1.69, p = 0.083). Conclusion Stress hyperglycemia ratio is closely related to the progression of non target lesions. This study provides a novel insight for optimizing the long-term management of non target lesions after PCI.